Extensively drug-resistant tuberculosis in Africa: prevalence and factors associated: a systematic review and meta-analysis - Kosmas, Petrus Ndiiluka (Department of Public Health and Family Medicine, 2020)
Background: There is a dearth of information regarding prevalence of extensively drugresistant tuberculosis (XDR-TB) in Africa. Although countries in Africa conduct national tuberculosis surveys on a regular basis, this information has not been systematically reviewed to ascertain the overall prevalence of XDR-TB in Africa. Methods: The study aimed to perform a systematic review and meta-analysis of the prevalence and factors associated with prevalence of pulmonary XDR-TB among adults in Africa. Eligible studies, published between 2006 and 2018, were sourced from various electronic databases including PubMed, Scopus, and Web of Science. Meta-analysis was performed using STATA (version 14.2) statistical software. The protocol of this review was registered with PROSPERO, reg No CRD42018117037. Result: A total of 6242 records were retrieved. Forty-eight studies were screened for eligibility and seven, which varied in terms of country setting and study design, were included. The prevalence of XDR-TB is 4% (95%CI 2-7) among participants tested for second-line anti-TB drug resistance, and 3% (95%1-6) among participants with drug resistant TB. The prevalence of XDR-TB was 7% (95%CI 1-18) among participants with MDR-TB. A few studies reported on the factors associated with the prevalence of XDR-TB. Discussion: The reported prevalence of XDR-TB among participants tested for second-line anti-TB drug resistance is low compared to WHO estimates. The systematic review underscores a dearth of studies depicting the reality regarding the prevalence of XDR-TB in Africa. Policymakers and stakeholders interested in drug-resistant TB should apply prudence when considering XDR-TB prevalence reported for Africa.